THE EFFECT OF LONG BOIL BLACK CASSUM (Manihot aipiphol) ON THE PRESENCE OF BACTERIA - Masbait, Meske; Rehena, Johanis Fritzgal; Pattipeilohy, Mery (Universitas Pattimura, 2021)
Processing of black cassava has the possibility of microbial contamination because the fermentation process is carried out in the open, black cassava in the open, at room temperature, allowing microbes such as bacteria to grow. The aim of this research is to determine the length of time for boiling cassava and the presence of bacteria, and to determine the appropriate boiling time that can inhibit the presence of bacteria. From the results of observations of cassava samples containing bacteria before boiling, this shows that fresh cassava used as raw material naturally contains a number of bacteria. Observing the colony characteristics of all bacterial isolates counted and uncounted, it was found that there were similarities and differences in properties, where the results of the analysis showed that the long boiling time treatment had a great influence on the morphology of the bacteria, namely round and wrinkled, with smooth and grooved edges, raised elevations, flat and thick. The color of the bacteria on black cassava is the same, namely white, with treatment times of 10, 20, 30 minutes. The boiling time treatment has a very significant effect on the shape, edges and elevation in the presence of bacteria. The presence of bacteria in black cassava before boiling shows that it naturally contains a number of bacteria, with long boiling treatment the number of bacteria increases.